Dynamic response of aerodynamic flutter of blooie line during gas drilling in mountain areas - Dianchen Liu; Peng Yang; Ke Deng; Shijie Tian; Hai Yan; Hongtao Li (AIP Advances)
Gas drilling technology remains a superior method for discovering and protecting oil and gas reservoirs in the petroleum exploration and development industry. However, its widespread application and further advancement have been significantly hindered by safety risks associated with surface equipment. Owing to the constraints of mountainous terrain, the connection of the blooie line inevitably adopts multiple elbow connections. As a result, aerodynamic flutter will occur when high-speed gas flow enters the blooie line, which threatens drilling safety. In this study, a series of comprehensive two-way fluid–structure interaction numerical simulations are conducted on the blooie line with multiple bends to determine its structural responses of the aerodynamic flutter induced by a sudden high-speed gas flow during gas drilling. The results suggest that a large quantity of rock cuttings and rock fragments, suddenly ejected when a high-production reservoir was unexpectedly encountered during drilling, tends to accumulate at the bends, leading to blockages and a reduction in the circulation area. This blockage is found to expose the blooie line to a significant risk of fracture, thereby threatening its structural integrity. The higher the gas production, the more severe the aerodynamic flutter of the blooie line. To address the challenge of blockage on the flutter, novel tank equipment is designed to effectively manage the sudden ejection of massive cuttings, aiming to prevent abrupt blockages in the blooie line during the drilling process. The application of this equipment, integrated into the blooie line, ensures the safety of gas drilling operations.